PENGARUH KATUP EKSPANSI TERMOSTATIK DAN PIPA KAPILER TERHADAP PERFOMANSI MESIN PENDINGIN SIKLUS KOMPRESI UAP MENGGUNAKAN REFRIGERAN HIDRKARBON - Izzuddin Ali Raja Siregar (Jurnal Sains dan Teknologi, 2022)
Expansion device is an important part of vapor compression cycle refrigeration machine which functions to lower the pressure of the liquid refrigerant coming out of the condenser and regulates the flow of refrigerant into the evaporator flow into the evaporator. In addition to the expansion device, another important thing is the use of refrigerant. A good refrigerant is a refrigerant that has a high latent heat, energy efficient, and also environmentally friendly. So it is important to know the performance of a cooling machine with hydrocarbon refrigerant. From these tests, the COP results of capillary pipes of 1.25 m using HCR-134a of 5.6, 1.5 m capillary pipe of 5.8, 2.7 m capillary pipe of 5.6, and 2.7 m capillary pipe of 5.8, 2.7 m capillary pipe of 5.3, and COP for KET of 5.4. The COP of capillary pipe 1.5 m capillary pipe has the greatest value because the evaporator and condenser pressures are the lowest. The use of HCR-134a increases the COP of the 1.25 m and 1.5 m capillary pipes compared to the use of R-134a, with the use of more efficient electrical power. However, the 2.7 m and KET capillary pipes caused lower COP and higher electrical power.